Farmers' adaptive behaviors to climate change and their influencing factors: evidence from the Guanzhong Region of Shaanxi, China - Song, Hongcheng; Zhu, Zhiyuan (Frontiers in Sustainable Food Systems, 2025)
Climate change poses escalating threats to agricultural systems worldwide, particularly for smallholder farmers in climate-sensitive regions. This study examines the adaptive behaviors of farmers and their determinants in the Guanzhong region of Shaanxi Province, China, using survey data from 1,000 households. Guided by Protection Motivation Theory (PMT), we focus on three adaptation strategies: crop structure adjustment, irrigation investment, and agricultural insurance uptake. Logit and Poisson regression models are employed to identify the effects of climate risk perception, training, self-efficacy, institutional access, and resource capacity on adaptive actions. The results reveal that perceived severity of climate change and agricultural training significantly increase the likelihood of adopting adaptation behaviors, particularly among low-income farmers. Self-efficacy is positively associated with insurance adoption, while income and landholding primarily influence capital-intensive adaptations such as irrigation. Cooperative membership and policy support enhance institutional forms of adaptation, notably insurance uptake. A robustness check using a Probit model and heterogeneity analysis by income group further confirm the consistency of findings. This study provides new empirical evidence on the psychological and structural drivers of climate adaptation and underscores the importance of integrated policy design combining awareness building, capacity development, and differentiated incentives to enhance farm-level resilience in semi-arid regions.